Community Policing: An Essential Strategy for Checkmating Crime and Terrorism in Nigeria: A Case Study Of Gombe State - Osah, Goodnews; Osita, Adah (NIU Journal of Social Sciences, 2017)
This study interrogated the philosophy and strategy of community â€“ oriented policing as an instrument for curbing terrorism in Nigeria. The study employed descriptive method and adopted Asset to liability shift theory. The study revealed that community-oriented policing is a potent weapon in the quiver of the government and various communities to stem the flow or tide of terrorism in Nigeria. Community-oriented policing is comprised of three key operational strategies namely, Trust Partnership, Organizational Transformation and problem solving. The study further revealed that the implementation of the operational strategies of community-oriented policing is one besieged by many and various challenges which include lack of trust, corruption, and human right abuses. The study concluded that the adoption of community-oriented policing is warmly welcomed to create safe environment in Nigeria. The study recommended a shift in the culture of the conventional law enforcement agencies to integrate the paradigm of community-oriented policing. A comprehensive training approach involving the community members and law enforcement agencies is also crucial in order to institutionalize the philosophy and strategy of community-oriented policing in the world of law enforcement agencies in Nigeria.      Keywords: Terrorism, Community policing, Community partnership, Organizational Transformation